Building resilient maize production systems with stress-adapted varieties : Farmers' priorities in western Kenya - Marenya, Paswel Phiri; Wanyama, Rosina; Alemu, Solomon; Woyengo, Vincent (Frontiers Media, 2022)
Maize cropping systems in Kenya, as is true in many other places in Africa, face multiple biotic and abiotic stressors not least climatic ones. Guided by farmers' priorities, maize breeding programs can contribute to the needed resilience against these changes by developing and mainstreaming new generations of maize varieties adapted to these challenges. Using data from 1,400 farmers and applying a multi-criteria choice analysis, this study reports on smallholder farmers' relative valuation of stress tolerance traits. The results showed that farmers were willing to pay significant premiums for tolerance to drought, striga, low nitrogen (nitrogen use efficiency) and fall army worm infestation, in that order. Large scale incorporation of these traits in legacy varieties as well as new ones, can contribute to enhancing maize system resilience and adaptation to changing growing conditions. For seed systems development, these traits can provide the basis for making strong business cases for the replacement of old varieties with new, stress-adapted ones.